PENGARUH HARGA DAN KUALITAS PRODUK SEBAGAI PENENTU KEPUASAN NASABAH PT BANK MUAMALAT INDONESIA, TBK KCU MEDAN SUDIRMAN - Asiah; Marlya Fatira AK; Rizal Agus (Politeknik Negeri Medan, 2020)
This research was conducted to determine the effect of the price and quality of the iB Muamalat Savings product on Customer Satisfaction at PT Bank Muamalat Indonesia, Tbk KCU Medan Sudirman. The research method is using questioners with the number of respondents are 137 orang. The data analysis method is using multiple linear regression by using SPSS 22. The results of this study indicate the price has a strong and significant positive effect of 0.550 on customer satisfaction at PT Bank Muamalat Indonesia, Tbk KCU Medan Sudirman and the quality of iB Muamalat Savings products have a strong and significant positive effect amounting to 0.711 to customer satisfaction at PT Bank Muamalat Indonesia, Tbk KCU Medan Sudirman. The price and quality of the iB Muamalat Savings product simultaneously have a positive and significant effect with the coefficient of determination (R2) of 0.526, which mean the ability of the price and quality of iB Muamalat Savings products to customer satisfaction at PT Bank Muamalat Indonesia, Tbk KCU Medan Sudirman affects the variation of ups and downs customer satisfaction at PT Bank Muamalat Indonesia, Tbk KCU Medan Sudirman amounted to 52.6% while the remaining 47.4% was influenced by other variables not include in this study.